Socioeconomic deprivation and mortality after emergency laparotomy: an observational epidemiological study - Poulton, Thomas E; Moonesinghe, Ramani; Raine, Rosalind; Martin, Peter (British journal of anaesthesia : BJA, 2020)
Socioeconomic circumstances can influence access to healthcare, the standard of care provided, and a variety of outcomes. This study aimed to determine the association between crude and risk-adjusted 30-day mortality and socioeconomic group after emergency laparotomy, measure differences in meeting relevant perioperative standards of care, and investigate whether variation in hospital structure or process could explain any difference in mortality between socioeconomic groups. This was an observational study of 58 790 patients, with data prospectively collected for the National Emergency Laparotomy Audit in 178 National Health Service hospitals in England between December 1, 2013 and November 31, 2016, linked with national administrative databases. The socioeconomic group was determined according to the Index of Multiple Deprivation quintile of each patient's usual place of residence. Overall, the crude 30-day mortality was 10.3%, with differences between the most-deprived (11.2%) and least-deprived (9.8%) quintiles (P<0.001). The more-deprived patients were more likely to have multiple comorbidities, were more acutely unwell at the time of surgery, and required a more-urgent surgery. After risk adjustment, the patients in the most-deprived quintile were at significantly higher risk of death compared with all other quintiles (adjusted odds ratio [95% confidence interval]: Q1 [most deprived]: reference; Q2: 0.83 [0.76-0.92]; Q3: 0.84 [0.76-0.92]; Q4: 0.87 [0.79-0.96]; Q5 [least deprived]: 0.77 [0.70-0.86]). We found no evidence that differences in hospital-level structure or patient-level performance in standards of care explained this association. More-deprived patients have higher crude and risk-adjusted 30-day mortality after emergency laparotomy, but this is not explained by differences in the standards of care recorded within the National Emergency Laparotomy Audit.